The Influence of Financial Ratios on Retail Firm Profitability in Indonesia - Lilis Setiawati; Erwin Budianto (Program Studi Keuangan & Perbankan, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2026)
This research aims to test and analyze the impact of the debt-to-asset ratio (DAR), total asset turnover (TATO), and firm size on return on assets (ROA) in retail companies listed on the Indonesia Stock Exchange (IDX). A quantitative approach was adopted in this research because using secondary data obtained from retail companies' financial reports selected during the observation period. The sampling technique was performed using purposive sampling based on the established criteria to produce a specific sample meet the research requirements. The data were compiled and analyzed using multiple linier regresion for determine both of simultan and partial effects of independent variables on companies' profitability. The results of this research indicate that DAR, TATO, and firm size simultaneously have a significant effect on ROA. However, partially, DAR and firm size have a significant influence on ROA, while TATO does not show a significant effect. These findings imply that capital structure and firm size play an important role in influencing the profitability of retail companies. Therefore, this study provides useful insights for company management in formulating effective financial strategies, as well as for investors in making appropriate investment decisions to improve overall company performance. Keywords: DAR; TATO; Firm Size; ROA; Retail Companies